Obstetric Care in Poor Settings in Ghana, India, and Kenya - Mills, Samuel; Bos, Eduard; Lule, Elizabeth; Ramana, G.N.V.; Bulatao, Rodolfo (World Bank, Washington, DC, 2013)
Women are at much greater risk in childbirth in developing countries than in developed countries. This report explores why maternal mortality continues to be so high in developing countries, and why emergency obstetric services are little utilized, through research carried out in poor areas in Ghana (Kassena-Nankana district), India (Uttar Pradesh state), and Kenya (Nairobi slums). The study employed both quantitative (household surveys, verbal autopsies, and health facilities surveys) and qualitative (focus groups and in-depth interviews) methods. Among the three settings, maternal mortality ratio was highest in the Nairobi slums, followed by Uttar Pradesh, while the Kassena- Nankana district had the lowest. It is intriguing that among the three settings, Nairobi slums had the highest proportion of women (70 percent) who sought professional assistance during delivery and yet the highest maternal mortality. One possible explanation is the different extent of legality of induced abortion in these three countries. Of the major causes of maternal mortality, the largest contrast among the study areas involved complications of abortion, which were almost four times higher in the Kenya slums than in the north of Ghana or in Uttar Pradesh. A large proportion of health facilities assessed in the three study areas were not capable of providing all six elements of basic emergency obstetric care.